2019
DOI: 10.1126/science.aaw4226
|View full text |Cite
|
Sign up to set email alerts
|

Inception of memories that guide vocal learning in the songbird

Abstract: Animals learn many complex behaviors by emulating the behavior of more experienced individuals. This essential, yet still poorly understood, form of learning relies on the ability to encode lasting memories of observed behaviors. We identified a vocal-motor pathway in the zebra finch where memories that guide learning of song-element durations can be implanted. Activation of synapses in this pathway seeds memories that guide learning of song-element duration and can override learning from social interactions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…In a combined NIf/HVC model, these NIf ensembles are sufficient to train downstream premotor sequences in HVC. Finally, in light of recent optogenetics results 62 , we model how NIf may play a role specifying the durations of song syllables.…”
mentioning
confidence: 99%
“…In a combined NIf/HVC model, these NIf ensembles are sufficient to train downstream premotor sequences in HVC. Finally, in light of recent optogenetics results 62 , we model how NIf may play a role specifying the durations of song syllables.…”
mentioning
confidence: 99%
“…Proportions of NCM firing and burst type neurons changed over the sensory learning period. The NCM has been suggested to be involved in song learning in males, especially as one of the sites for storing tutor song memories (Bolhuis and Gahr, 2006 ; Hahnloser and Kotowicz, 2010 ; Bolhuis and Moorman, 2015 ), while other brain areas in the song system have also been suggested as tutor song memory loci (Mackevicius and Fee, 2018 ; Zhao et al, 2019 ). On the other hand, in females, the NCM is thought to be involved in song discrimination (Tomaszycki and Blaine, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Formed memories of tutor songs are thought to guide later motor song learning in males (Brainard and Doupe, 2002 ; Bolhuis and Gahr, 2006 ; Theunissen and Shaevitz, 2006 ) and also to affect auditory cognitive functions of females in later auditory learning (Chen et al, 2017 ; Diez et al, 2019 ). Accumulating evidence suggests that memories of tutor songs for male juvenile song learning are formed in the caudomedial nidopallium (NCM), which is analogous to the mammalian higher auditory cortex, while other studies have suggested the presence of tutor song memories in the song motor area (Mackevicius and Fee, 2018 ; Zhao et al, 2019 ). A greater number of NCM neurons express the immediate early gene, ZENK, in zebra finches that are exposed to experienced tutor songs than in those that are exposed to novel conspecific songs (Terpstra et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile birds can memorize the song of a tutor at any time between 20-60 dph, but they don’t start to practice singing until approximately 35-40 dph (Fig 1a). This developmental progression and the ability to raise birds in groups without a song-tutor – hereby referred to as ‘isolates’ – allowed us to knock down FoxP1 expression prior to behavioral imitation of song, either before or after birds had an opportunity to form a memory of a tutor-song 16 (Fig. 2a: tutoring pre-FP1-KD, referred to as ‘behavioral imitation’ group ( FP1-KD BI ), Fig.2e: tutoring post-FP1-KD, referred to as ‘social experience’ group ( FP1-KD SE )).…”
Section: Knockdown Of Foxp1 In Hvc Blocks Learning From Social Experimentioning
confidence: 99%